Reflective practice as a fuel for organizational learning - Sanna Hilden; Kati Tikkamäki (Administrative Sciences, 2013)
Learning theories and their interpretations in management research recognize the role of reflection as a central element in the learning process. There also exists a broad consensus that organizational learning (OL) happens at three intertwined levels of the individual, the group and the organization. This tri-level analysis has been most influentially presented by Crossan, Lane and White (1999), as a premise for their 4I framework of OL. Though the 4I framework builds strongly on existing literature on OL, it does not address the role of reflection as a factor operating between the inputs and outcomes in 4I sub-processes. Though a large body of research exists regarding the notion of reflection and its importance in terms of OL, this has not been discussed in the specific context of the 4I framework. This article contributes to the development of the 4I model by discussing how reflective practice-on three levels and within 4I sub-processes-fuels the OL process. The argumentation is based on an extensive literature review in three dimensions of learning, illustrated with an empirical inquiry into three business organizations and their reflective practice. In addition, the aim is to increase the understanding of reflection as not only an individual or group process, but as an organized practice, enabled by the tools of management control.
Keywords: 350; organizational learning; reflective practice; 4I framework; management control